The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11030-021-10375-4
|View full text |Cite
|
Sign up to set email alerts
|

A review on synthetic account of 1,2,4-oxadiazoles as anti-infective agents

Abstract: Graphical abstract Most of the currently marketed drugs consist of heterocyclic scaffolds containing nitrogen and or oxygen as heteroatoms in their structures. Several research groups have synthesized diversely substituted 1,2,4-oxadiazoles as anti-infective agents having anti-bacterial, anti-viral, anti-leishmanial, etc. activities. For the first time, the present review article will provide the coverage of synthetic account of 1,2,4-oxadiazoles as anti-infective agents along with their potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…7 a). Biologically divergent 1,2,4-oxadiazole derivative ( 8 ) [ 55 ] has been tightly accommodated with several solvent molecules and surrounded by amino acid residues in the active site of spike glycoprotein (Fig. 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…7 a). Biologically divergent 1,2,4-oxadiazole derivative ( 8 ) [ 55 ] has been tightly accommodated with several solvent molecules and surrounded by amino acid residues in the active site of spike glycoprotein (Fig. 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…Last decade has witnessed a paradigm shift in the way molecules are being synthesized specially the Ncontaining heterocycles. [3][4][5][42][43][44] In order to address some of the most burning questions of 21 st century i. e., the climate change and environment degradation, all domains of science and research have resorted to greener and sustainable protocols. Therefore into this pursuit, it is highly imperative to adapt to environmentally benign approaches for the synthesis of bioactive heterocycles.…”
Section: Sustainable Methods For Synthesis Of Quinolinesmentioning
confidence: 99%
“…Their prevalence could be understood with the fact that approximately ∼ 60 % of heterocycles amongst the drug candidate molecules possess nitrogen as heteroatom. [1,2] Some of the important N-containing heterocycles are indole, oxadiazole, pyrrole, quinoline, pyridine, quinazoline and quinoxaline [3][4][5][6] so on and so forth. These Ncontaining heterocycles found to possess broad spectrum of biological activities and are therefore considered as a most privileged class of biologically active chemical class utilized in medicinal chemistry (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[18] On the another part, the innovative and green synthetic strategies have given a new era of synthesis of diversely substituted heterocycles. [19][20][21] Towards the on-going research endeveour on anti-TB agents, [22][23][24][25][26][27][28][29] recently we have reported the quinquennial account of diverse scaffolds in search of agents having anti-TB profile reported during 2016-2020. [30] In this review, we have shed light on candidates having anti-TB activity (minimum inhibitory concentration, MIC or hald maximal inhibitory concentrationm IC 50 of 20 μg/mL or μM) reported during 2021 retrieved through Sci-Finder [31] to educate the reader of the present work to update with the on-going trends on design of newly identified anti-tubercular agents.…”
Section: Diverse Scaffolds Reported For Anti-tb Activitymentioning
confidence: 99%